2021
DOI: 10.3390/app112311162
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced DQN Framework for Selecting Actions and Updating Replay Memory Considering Massive Non-Executable Actions

Abstract: A Deep-Q-Network (DQN) controls a virtual agent as the level of a player using only screenshots as inputs. Replay memory selects a limited number of experience replays according to an arbitrary batch size and updates them using the associated Q-function. Hence, relatively fewer experience replays of different states are utilized when the number of states is fixed and the state of the randomly selected transitions becomes identical or similar. The DQN may not be applicable in some environments where it is neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Jian Zheng et al used partial mutual information (PMI) [ 49 ] and correlation matching-based active learning (CMAL) [ 50 ] to suggest a technique to reduce the amount of training data [ 51 ]. Gu et al suggested a method to reduce the amount of training data by grouping the training data of the Gomoku game in similar states together with an ANN [ 52 , 53 ]. This method significantly reduced the amount of training data and induced the DNN to select the next best solution through the action filter.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Jian Zheng et al used partial mutual information (PMI) [ 49 ] and correlation matching-based active learning (CMAL) [ 50 ] to suggest a technique to reduce the amount of training data [ 51 ]. Gu et al suggested a method to reduce the amount of training data by grouping the training data of the Gomoku game in similar states together with an ANN [ 52 , 53 ]. This method significantly reduced the amount of training data and induced the DNN to select the next best solution through the action filter.…”
Section: Related Workmentioning
confidence: 99%
“…As the UX dataset for each user can be an imbalanced dataset, overfitting may occur when learning without preprocessing. In this paper, the amount of data is reduced by grouping similar UX data within the same class and selecting representative data based on the similarity calculated by ANN [ 52 , 53 ]. Figure 4 shows the flowchart of the ANN-based clustering method.…”
Section: Ux Framework Of Game Agent Systemmentioning
confidence: 99%